2018
DOI: 10.1016/j.heliyon.2018.e00968
|View full text |Cite
|
Sign up to set email alerts
|

A search for training of practising leadership in emergency medicine: A systematic review

Abstract: ObjectiveThis systematic review examines the medical, psychological and educational literature for training in practising leadership of a team leader in emergencies. The objectives of this paper are (1) describe how literature addresses operational training in practising leadership for the emergency medical team-leader (2) enhance understanding of leadership training in the medical environment.BackgroundWorldwide, medical supervisors find it difficult to get students to rise to the occasion as leaders of emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…The previously mentioned systematic review suggested in addition that it is necessary to work with the personal challenges associated with stressful situations. As a consequence, it is necessary to work with the resident's courage, self-confidence and authority when he or she acts as a team leader [24]. This is further supported by three studies, Hunziker et al.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The previously mentioned systematic review suggested in addition that it is necessary to work with the personal challenges associated with stressful situations. As a consequence, it is necessary to work with the resident's courage, self-confidence and authority when he or she acts as a team leader [24]. This is further supported by three studies, Hunziker et al.…”
Section: Introductionmentioning
confidence: 82%
“…As previously described in the mentioned systematic review [24], leadership is acquired through practice, and therefore leadership competencies should be acquired not through theoretical learning, but through practice as described by Mintzberg [25]. In accordance with this, surgeons learn to sew a wound together by doing it in practice.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The simulation scenario also helps students to understand that the leader is not necessarily the older person but the one that better faces and solves specific situations, at specific moments. Everyone´s opinion is a valuable input for every situation, and a lack of leadership could be highly detrimental to performance during a critical situation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Also, behavior was less tested in the first years since at that time residents are not alone and do not make clinical decisions. Given this implies less leadership, non-technical skills were not considered important [ 22 ]. However, and over the years, students had no doubts about the impact of behavior in critical situations, which is clearly reflected on the fourth-year being the one that attributed more importance to behavioral questions.…”
Section: Discussionmentioning
confidence: 99%